Cathode active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2024221414
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-09
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-08-28
Smart Images

Figure 2025028269000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery using the positive electrode active material. [Background technology]
[0002] In recent years, lithium transition metal composite oxides with a high Ni content have been attracting attention as positive electrode active materials with high energy density. For example, Patent Document 1 discloses a method of coating the particle surfaces of lithium transition metal composite oxides with a boric acid compound in order to suppress gas generation due to electrolyte decomposition on the surface of the positive electrode active material in a charged state. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-40382 A Summary of the Invention
[0004] However, in non-aqueous electrolyte secondary batteries such as lithium ion batteries, when B is present in the form of a boric acid compound or the like on the particle surface of a lithium transition metal composite oxide, the decomposition of the electrolyte is suppressed and the heat resistance of the battery is improved, but the resistance value of the battery increases and the rate characteristics are deteriorated. The technology disclosed in Patent Document 1 still has room for improvement in terms of achieving both improvement of the heat resistance of the battery and suppression of deterioration of the rate characteristics.
[0005] An object of the present disclosure is to achieve both improved heat resistance and suppression of deterioration in rate characteristics in a nonaqueous electrolyte secondary battery including a high-energy density positive electrode active material.
[0006] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure is a positive electrode active material that includes a lithium transition metal composite oxide containing 80 mol % or more of Ni relative to the total number of moles of metal elements excluding Li, and B is present at least on the particle surface of the composite oxide. When particles having a particle size larger than the 70% particle size (D70) on a volume basis are defined as first particles and particles having a particle size smaller than the 30% particle size (D30) on a volume basis are defined as second particles, the molar fraction of B relative to the total number of moles of metal elements excluding Li in the second particles is larger than the molar fraction of B relative to the total number of moles of metal elements excluding Li in the first particles.
[0007] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the above positive electrode active material, a negative electrode, and a non-aqueous electrolyte.
[0008] According to the positive electrode active material of one embodiment of the present disclosure, a nonaqueous electrolyte secondary battery that achieves both improved heat resistance and suppressed deterioration of rate characteristics can be provided. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present inventors have conducted extensive research to solve the above problems, and have found that the heat resistance of a battery can be improved while suppressing a decrease in rate characteristics by increasing the molar fraction of B in the second particles having a small particle size compared to the molar fraction of B in the first particles having a large particle size. Here, the first and second particles are secondary particles formed by aggregation of primary particles of a lithium transition metal composite oxide. A lithium transition metal composite oxide having a high Ni content and a high energy density has a high average valence of Ni during charging, so that the electrolyte is easily decomposed by a side reaction with the electrolyte, which adversely affects the heat resistance of the battery. As described in Patent Document 1, the above side reaction can be suppressed by having B exist on the surface of the secondary particles of the lithium transition metal composite oxide in the form of a boric acid compound or the like, but there is a problem that the resistance of the battery increases, resulting in a decrease in rate characteristics. Therefore, by adjusting the molar fraction of B in the first particles having a large particle size and the second particles having a small particle size, and increasing the molar fraction of B in the second particles having a large surface area per unit mass, the side reactions with the electrolyte were effectively suppressed, while by decreasing the molar fraction of B in the first particles, the molar fraction of B present in the entire lithium transition metal composite oxide was reduced, thereby successfully suppressing the deterioration of the rate characteristics.
[0011] Hereinafter, an example of an embodiment of the positive electrode active material for nonaqueous electrolyte secondary batteries according to the present disclosure and a nonaqueous electrolyte secondary battery using the positive electrode active material will be described in detail. Hereinafter, a cylindrical battery in which a wound electrode body 14 is housed in a cylindrical outer can 16 with a bottom will be exemplified, but the outer can is not limited to a cylindrical outer can, and may be, for example, a rectangular outer can, or may be an outer can made of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body may be a laminated type electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators interposed therebetween.
[0012] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in FIG. 1, the nonaqueous electrolyte secondary battery 10 includes a wound electrode assembly 14, a nonaqueous electrolyte, and an exterior can 16 that accommodates the electrode assembly 14 and the electrolyte. The electrode assembly 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The exterior can 16 is a cylindrical metal container with a bottom that is open on one axial side, and the opening of the exterior can 16 is closed by a sealing body 17. In the following description, for convenience of explanation, the sealing body 17 side of the battery is referred to as the top, and the bottom side of the exterior can 16 is referred to as the bottom.
[0013] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles, amides, and mixed solvents of two or more of these are used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. For the electrolyte salt, for example, a lithium salt such as LiPF6 is used. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte using a gel-like polymer or the like.
[0014] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all long strip-shaped bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The negative electrode 12 is formed to be slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the longitudinal direction and the width direction (short direction). The two separators 13 are formed to be at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0015] Insulating plates 18 and 19 are disposed above and below the electrode body 14. In the example shown in Fig. 1, the positive electrode lead 20 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and the negative electrode lead 21 passes outside the insulating plate 19 and extends toward the bottom side of the outer casing 16. The positive electrode lead 20 is connected to the lower surface of an internal terminal plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom inner surface of the outer casing 16 by welding or the like, and the outer casing 16 serves as a negative electrode terminal.
[0016] A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 formed therein, with part of the side surface protruding inward, to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the top of the exterior can 16 by the grooved portion 22 and the open end of the exterior can 16 which is crimped against the sealing body 17.
[0017] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0018] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the positive electrode active material that constitutes the positive electrode 11, will be described in detail below.
[0019] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film with the metal disposed on the surface layer, or the like can be used. The positive electrode composite layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core except for the part to which the positive electrode lead 20 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode composite layer on both sides of the positive electrode core.
[0020] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).
[0021] The positive electrode active material includes particles of a lithium transition metal composite oxide containing 80 mol % or more of Ni relative to the total number of moles of metal elements excluding Li. By making the Ni content 80 mol % or more, a high-capacity battery can be obtained. In addition, B is present at least on the particle surface of the lithium transition metal composite oxide. Hereinafter, for convenience of explanation, the lithium transition metal composite oxide is referred to as "composite oxide (Z)". The positive electrode active material may be mainly composed of the composite oxide (Z) and may be substantially composed of only the composite oxide (Z). The positive electrode active material may include a composite oxide other than the composite oxide (Z) or other compounds within a range that does not impair the object of the present disclosure.
[0022] The composite oxide (Z) may contain a metal element other than Li, Ni, and B. Examples of the metal element include Co, Mn, Al, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Ti, and Si. One example of a suitable composite oxide (Z) is represented by the general formula Li a Ni b Co c M1 d M2 e B f O g (wherein, 0.8≦a≦1.2, b≧0.80, c≦0.15, 0.01≦d≦0.12, 0≦e≦0.05, 0.001≦f≦0.020, 1≦g≦2, b+c+d+e+f=1, M1 is at least one element selected from Mn and Al, and M2 is at least one element selected from Groups 4 to 6). That is, the molar fraction of B relative to the total moles of metal elements excluding Li is preferably 0.001 to 0.020, and more preferably 0.005 to 0.015. The molar fraction of metal elements in the entire particle of the complex oxide (Z) is measured by inductively coupled plasma (ICP) emission spectrometry. From the viewpoint of capacity and heat resistance, M1 is preferably Mn.
[0023] The composite oxide (Z) is, for example, a secondary particle formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particle is, for example, 0.05 μm to 1 μm. The particle size of the primary particle is measured as the diameter of a circumscribed circle in a particle image observed by a scanning electron microscope (SEM). B is present on the surface of the secondary particle of the composite oxide (Z), and may also be present on the surface of the primary particle inside the secondary particle or at the grain boundary. In addition, a part of B may also be present inside the primary particle, and may form a solid solution with other metal elements contained in the composite oxide (Z).
[0024] The composite oxide (Z) is a particle having a volume-based median diameter (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 means a particle diameter at which the cumulative frequency is 50% from the smallest particle diameter in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction type particle size distribution measuring device (e.g., MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as a dispersion medium.
[0025] The composite oxide (Z) is characterized in that, when particles having a volumetric particle size larger than the 70% particle size (D70) are defined as first particles and particles having a volumetric particle size smaller than the 30% particle size (D30) are defined as second particles, the molar fraction of B in the second particles is higher than the molar fraction of B in the first particles. This makes it possible to simultaneously improve the heat resistance of the battery and suppress the deterioration of the rate characteristics. B is contained in both the first particles and the second particles.
[0026] Here, D70 means a particle size where the cumulative frequency is 70% from the smallest particle size in the volumetric particle size distribution. Similarly, D30 means a particle size where the cumulative frequency is 30% from the smallest particle size in the volumetric particle size distribution. For example, D70 is 9 μm to 19 μm, and D30 is 3 μm to 13 μm. In addition, the molar fraction of metal elements present on the particle surface of the complex oxide (Z) is measured by X-ray photoelectron spectroscopy (XPS). By setting the X-ray irradiation spot diameter to 1 mmΦ or more, several hundred particles of the complex oxide (Z) are contained within the irradiation spot, so that the molar fraction of B on the surface of the complex oxide (Z) can be measured on average.
[0027] On the surface of the first particle and the surface of the second particle, the molar fraction of B relative to the total number of moles of metal elements excluding Li (hereinafter sometimes referred to as "surface coverage of B") can be 50% to 98%. Within this range, the heat resistance of the battery can be improved while suppressing a decrease in battery capacity. Here, the surface coverage of B can be calculated from the molar fraction of B relative to the total number of moles of metal elements excluding Li measured by XPS on the secondary particle surface.
[0028] On the surfaces of the first and second particles, B may be present in the form of a boron compound containing Li and B. As the B source, boron compounds such as boric acid (H3BO3), boron oxide (B2O3), and lithium borate (LiBO2, Li2B4O7) are used. When boric acid or boron oxide is used as the B source, it may react with Li present on the particle surface or a Li source added separately during firing to produce a boron compound containing Li and B.
[0029] The boron compound may be formed so as to cover the entire surface of the secondary particle, or may be scattered on the surface of the secondary particle. In the case of particulate form, the particle size of the boron compound is generally smaller than the particle size of the primary particles constituting the composite oxide (Z). The particles of the boron compound can be confirmed by SEM. It is preferable that the boron compound is attached over a wide area without being unevenly distributed on a part of the surface of the secondary particles constituting the composite oxide (Z).
[0030] Furthermore, the thickness of the boron compound on the surfaces of the first particles and the second particles is not particularly limited, and can be, for example, 10 nm to 100 nm.
[0031] As described above, in the composite oxide (Z), B may be present inside the primary particles and may be dissolved in a solid solution with a transition metal element such as Ni. The molar fraction of B relative to the dissolved metal element can be confirmed by energy dispersive X-ray spectroscopy (EDS) in the cross section of the primary particle. In the composite oxide (Z), the total molar number of B in a solid solution state and B in a boron compound state present on the surface is preferably 0.001 to 0.020 relative to the total molar number of metal elements excluding Li.
[0032] The composite oxide (Z) can be prepared, for example, by the following procedure. (1) Two types of Li-free composite compounds (X1) and (X2) with different D50s are calcined by adding a Li source such as lithium hydroxide to them, to synthesize lithium composite oxides (Y1) and (Y2) with different D50s. An example of the composite compound is a composite oxide or hydroxide containing Ni, Co, and Mn. At this time, one type of lithium composite oxide may be classified to obtain lithium composite oxides with two types of average particle sizes. A conventionally known method may be applied to the classification. The obtained lithium composite oxides (Y1) and (Y2) may be washed with water. By washing with water, not only the amount of Li present on the surface of the lithium composite oxides (Y1) and (Y2) but also the amount of Li present inside Y1 and Y2 is reduced, and voids are generated inside the washed Y1 and Y2. (2) A B source is added to each of the composite oxides (Y1) and (Y2), and B is compounded on the particle surface, followed by calcination to synthesize composite oxides (Z1) and (Z2). Then, the composite oxides (Z1) and (Z2) are mixed to obtain composite oxide (Z). An example of the B source is boric acid (H3BO3). A dry particle compounding device (e.g., NOB-130, manufactured by Hosokawa Micron Corporation) is used for compounding. At this time, a Li source such as lithium hydroxide may be added together with the B source.
[0033] In the above step (2), by making the amount of H3BO3 added to the composite oxide (Y2) larger than the amount of H3BO3 added to the composite oxide (Y1), the molar fraction of B in the composite oxide (Z2) can be made larger than the molar fraction of B in the composite oxide (Z1).
[0034] The firing temperature in the above step (2) is, for example, 200°C to 500°C. By adjusting the firing temperature of the composite oxides (Y1) and (Y2), the surface coverage of B and the thickness of the boron compound in the composite oxide (Z1) and composite oxide (Z2) can be adjusted. By firing Y1 and Y2 together with the B source at a high temperature, composite oxides (Z1) and (Z2) having a low surface coverage of B on the particle surface can be synthesized. By firing Y1 and Y2 together with the B source at a low temperature, composite oxides (Z1) and (Z2) having a high surface coverage of B on the particle surface can be synthesized. The high temperature is, for example, 350°C to 500°C, and the low temperature is, for example, 200°C to 325°C. The relationship between the firing temperature and the coverage may change depending on the composition and shape of the lithium transition metal composite oxide, the firing time, the firing atmosphere, and the like.
[0035] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the part to which the negative electrode lead 21 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.
[0036] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.
[0037] The binder contained in the negative electrode mixture layer may be, as in the case of the positive electrode 11, a fluororesin, PAN, polyimide, acrylic resin, polyolefin, or the like, but it is preferable to use styrene-butadiene rubber (SBR). The negative electrode mixture layer preferably further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, or PAA or a salt thereof.
[0038] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator. EXAMPLES
[0039] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0040] <Example 1> [Synthesis of positive electrode active material] Obtained by coprecipitation, D50 is 12μm and the composition is Ni 0.85 Co 0.08 Mn 0.07 (OH)2 nickel cobalt manganese composite hydroxide and D50 8μm and composition Ni 0.85 Co 0.08 Mn 0.07 The nickel-cobalt-manganese composite hydroxides of (OH)2 were each calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide (X1) having a large average particle size and a nickel-cobalt-manganese composite oxide (Y1) having a small average particle size.
[0041] Next, lithium hydroxide and nickel-cobalt-manganese composite oxide (X1) having a large average particle size were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08:1. This mixture was fired at 700°C in an oxygen atmosphere for 8 hours and then pulverized to obtain lithium composite oxide (X2) having a large average particle size. The obtained lithium composite oxide (X2) was not washed with water.
[0042] Next, lithium hydroxide and nickel-cobalt-manganese composite oxide (Y1) having a small average particle size were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08:1. This mixture was fired at 700°C in an oxygen atmosphere for 8 hours and then pulverized to obtain lithium composite oxide (Y2) having a small average particle size. The obtained lithium composite oxide (Y2) was not washed with water.
[0043] Next, the lithium composite oxide (X2) having a large average particle size was dry-mixed with boric acid (H3BO3) so that the molar ratio of the total amount of Ni, Co, and Mn to B in H3BO3 was 1:0.005. This mixture was fired at 300°C in air for 3 hours and then pulverized to obtain a lithium composite oxide (X3) having B present on the particle surface.
[0044] Next, the lithium composite oxide (Y2) having a small average particle size was dry-mixed with H3BO3 so that the molar ratio of the total amount of Ni, Co, and Mn to B in H3BO3 was 1:0.015. This mixture was fired at 300°C in air for 3 hours and then pulverized to obtain a lithium composite oxide (Y3) having B present on the particle surfaces.
[0045] Next, the lithium composite oxides (X3) and (Y3) were mixed in a mass ratio of 1:1 to prepare a positive electrode active material. The amount of B present on the particle surface and inside the particles can be quantified by ICP. The presence of B on the particle surface in the form of a boron compound containing Li and B can be confirmed by XRD, XPS, XAFS, etc.
[0046] The composition of the positive electrode active material was analyzed by ICP, and Li 1.01 Ni 0.84 Co 0.08 Mn 0.07 B 0.01 O2. Therefore, from the results of ICP, the molar fraction of B relative to the total number of moles of metal elements (Ni, Co, Mn, B) excluding Li was 1.0%. In addition, as a result of analyzing the compositions of lithium composite oxides (X3) and (Y3) by ICP, the molar fraction of B relative to the total number of moles of metal elements (Ni, Co, Mn, B) excluding Li was 0.5% and 1.5%, respectively.
[0047] The surface coverage of B was calculated by measuring the number of moles of Ni, Co, Mn, and B on the secondary particle surface by XPS, and calculating the molar fraction of B relative to the total number of moles of Ni, Co, and Mn. The surface coverage of B was 96% for both lithium composite oxides (X3) and (Y3). The particle size distribution of the positive electrode active material was D50 12 μm, D70 14 μm, and D30 10 μm.
[0048] [Preparation of positive electrode] The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 96.3:2.5:1.2, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, followed by kneading to prepare a positive electrode composite slurry. The positive electrode composite slurry was applied to both sides of a positive electrode core made of aluminum foil, and the coating was dried. The coating was then rolled using a roller and cut to a predetermined electrode size to obtain a positive electrode in which a positive electrode composite layer was formed on both sides of the positive electrode core. An exposed portion was provided in part of the positive electrode, exposing the surface of the positive electrode core.
[0049] [Preparation of negative electrode] Natural graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite slurry. The negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, and the coating film was dried. The coating film was then rolled using a roller and cut to a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core. An exposed portion was provided in part of the negative electrode, where the surface of the negative electrode core was exposed.
[0050] [Preparation of non-aqueous electrolyte] Lithium hexafluorophosphate (LiPF6) was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4. Furthermore, vinylene carbonate (VC) was dissolved at a concentration of 2.0 mass% in the mixed solvent to prepare a non-aqueous electrolyte.
[0051] [Battery construction] An aluminum lead was attached to the exposed part of the positive electrode, and a nickel lead was attached to the exposed part of the negative electrode, and the positive and negative electrodes were spirally wound with a polyolefin separator interposed therebetween, and then pressed in the radial direction to produce a flat wound electrode body. This electrode body was housed in an exterior body made of an aluminum laminate sheet, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a nonaqueous electrolyte secondary battery with a design capacity of 650 mAh.
[0052] <Example 2> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that X2 and Y2 were each washed with water.
[0053] <Comparative Example 1> The same procedure as in Example 1 was repeated except that X2 and H3BO3 were mixed such that the molar ratio of the total amount of Ni, Co, and Mn to B in H3BO3 was 1:0.010, and Y2 and H3BO3 were mixed such that the molar ratio of the total amount of Ni, Co, and Mn to B in H3BO3 was 1:0.010.
[0054] <Comparative Example 2> The same procedure as in Example 2 was repeated except that X2 and H3BO3 were mixed such that the molar ratio of the total amount of Ni, Co, and Mn to B in H3BO3 was 1:0.010, and Y2 and H3BO3 were mixed such that the molar ratio of the total amount of Ni, Co, and Mn to B in H3BO3 was 1:0.010.
[0055] The rate characteristics and thermal runaway temperature were evaluated for each of the batteries of the examples and comparative examples. The evaluation results are shown in Table 1. Furthermore, Table 1 shows the molar fraction of B relative to the total number of moles of metal elements other than Li in the first particle and the second particle, and the surface coverage of B.
[0056] [Evaluation of rate characteristics] Each battery of the examples and comparative examples was charged at a constant current of 0.5 It in a temperature environment of 25°C until the battery voltage reached 4.2 V, and then constant voltage charging was performed until the current value reached 0.02 It at 4.2 V. The battery was then left for 15 minutes. Next, constant current discharging was performed at 0.05 It until the battery voltage reached 2.5 V, and the discharge capacity C1 at 0.05 It was measured. Next, constant voltage charging was performed at 4.2 V until the current value reached 0.02 It, and the battery was then left for 15 minutes. Then, constant current discharging was performed at 2 It until the battery voltage reached 2.5 V, and the discharge capacity C2 at 2 It was measured. The rate characteristics were calculated from the following formula.
[0057] Rate characteristic (%) = C2 / C1 x 100 [ARC Exam] The fabricated battery was charged at a constant current of 0.3 It in an environment of 25°C until the battery voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current value reached 0.05 It, to enter a charged state. After that, the battery was heated to 130°C in the ARC test device, and the self-heating rate (°C / min) of the battery in an adiabatic environment was measured by observing the battery temperature with a thermocouple attached to the flat part of the battery. The battery temperature when the self-heating rate of the battery reached 10°C / min was defined as the thermal runaway temperature.
[0058] [Table 1]
[0059] As shown in Table 1, the batteries of the Examples all had higher rate characteristics and thermal runaway temperatures than the batteries of the Comparative Examples. In other words, it can be seen that the batteries of the Examples both improved heat resistance and suppressed deterioration of rate characteristics. In Example 1, since no water washing was performed during synthesis of the positive electrode active material, a large amount of Li remained on the surface of the lithium composite oxide, resulting in good ion conductivity and higher rate characteristics than Example 2. [Explanation of symbols]
[0060] 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Grooved part 23 Internal terminal board 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket
Claims
1. A positive electrode active material comprising a lithium transition metal composite oxide containing 80 mol % or more of Ni relative to the total number of moles of metal elements excluding Li, and B being present at least on the particle surface of the lithium transition metal composite oxide, the content of B in the positive electrode active material is 0.001 or more and 0.020 or less, when the total number of moles of metal elements excluding Li contained in the lithium transition metal composite oxide is taken as 1, When a particle having a particle size larger than the 70% particle size (D70) based on volume is defined as a first particle, and a particle having a particle size smaller than the 30% particle size (D30) based on volume is defined as a second particle, a molar fraction of B relative to a total mole number of metal elements excluding Li in the second particles is greater than a molar fraction of B relative to a total mole number of metal elements excluding Li in the first particles.
2. The lithium transition metal composite oxide has the general formula Li a Ni b Co c M1 d M2 e B f O g (wherein 0.8≦a≦1.2, b≧0.80, c≦0.15, 0.01≦d≦0.12, 0≦e≦0.05, 0.001≦f≦0.020, 1≦g≦2, b+c+d+e+f=1, M1 is at least one element selected from Mn and Al, and M2 is at least one element selected from Groups 4 to 6.
3. 3 . The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , wherein B is present in a state of a boron compound containing Li and B on the surfaces of the first particles and the second particles.
4. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 3; A negative electrode; A non-aqueous electrolyte; A non-aqueous electrolyte secondary battery comprising:
Citation Information
Patent Citations
Positive electrode for lithium secondary battery, lithium secondary battery, and method for manufacturing positive electrode for lithium ion secondary battery
JP2017033839A
Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2018073481A
Positive electrode for non-aqueous electrolyte secondary battery
WO2015079664A1
Positive electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
WO2017098679A1
Positive electrode active material for nonaqueous rechargeable battery, and nonaqueous electrolyte rechargeable battery
WO2018043190A1